Valorization of okara biosorbent for heavy metal removal / Muhammad Farhan Ahmad ... [et al.] - Ahmad, Muhammad Farhan; Khalid, Nurul Maisarah; Abdul Aziz, Nur Syazwanie; Sayed Jamaludin, Sharifah Iziuna (2018)
Many of the industry has caused several damages to the water clue to release of toxic heavy metals. Heavy metals that discharge in the wastewater from industries such as lead, copper, zinc, cadmium, manganese which are very harmful to organisms and environment. ln the present study, okara was used as the material for adsorption of Pb2+ and Zn2 from simulated wastewater. The experiment was tested by using different parameters such as adsorbent dose and contact time. The treated and untreated okara was used to evaluate their potential as heavy metal removal. For the treated okara (TO), it undergoes ultrasonic-assisted alkaline as the pretreatment. Pretreatment of okara with NaOH increased the capacity of heavy metals adsorption compared to untreated okara (UTO) for both parameters. For Pb2+ solution, the highest adsorption percentage of treated okara for adsorbent close is at 5 g and the highest adsorption percentage of TO for contact time is at 40 min. However, for Zn2+ solution, the highest adsorption percentage of TO for adsorbent dose is at 20 g whereas the highest adsorption percentages of treated okara for contact time is at 140 min. Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) analysis was used to analyse the present of Pb2+ and Zn1+ and also to measure the quantity of heavy metals adsorption from the simulated wastewater. The most influence of parameters is contact time. The results showed that the adsorption capacity increases as the contact time increases.